Pengaruh Aktivitas Tektonik Terhadap Rekonstruksi Jalan Di Desa Pekan Gedang Dan Sekitarnya, Kecamatan Batang Asai, Kabupaten Sarolangun, Jambi - Sri Hayani; Edy Sutriyono (Universitas Muslim Indonesia, 2020)
The Semangko Fault is a regional fault stretching along the island of Sumatra, consisting of several segments with movements of 6-37 mm per year (Sieh et al., 2000). Administratively, the research area is located in Batang Asai District, Sarolangun Regency, Jambi. Based on its geographical location, the study area is included in the Semangko Fault zone with geological conditions composed by pre-Tertiary age rocks that have been deformed, both faults and hefty. Deformation that occurs continuously, is characterized by several reconstructions of damaged roads in the alignment zone. The analysis carried out on the DEM (Digital Elevation Model) image includes morphotectonic aspects and identification of the solid data and fault fields collected in the field in order to interpret the level of tectonic activity that affects the road reconstruction in the area. From the results of the analysis it was identified that tectonic activity in the area was very high according to the classification of El Hamdouni et al. (2008).